Implementasi Halal Supply Chain Management (HSCM) pada usaha mikro, kecil, dan menengah (UMKM) Pangan: Studi Kualitatif - Sutono; Izzah Sarirotun Nijwah; Zamrud Mirah Delima; Edi Wicaksono Abdurrosid (Universitas Muhammadiyah Palembang, 2026)
This study aims to examine the implementation of Halal Supply Chain Management (HSCM) among food micro, small, and medium enterprises (MSMEs). A qualitative descriptive approach was employed, with data collected through semi-structured interviews with MSME actors and a key informant from the Badan Penyelenggara Jaminan Produk Halal (BPJPH). The data were analyzed thematically to explore the understanding of halal, supply chain practices, and implementation challenges. The findings indicate that although MSMEs demonstrate a relatively high level of halal awareness, HSCM implementation remains partial and largely administrative. Upstream supply chain practices, particularly in raw material procurement, are predominantly informal and trust-based, increasing potential halal-related risks. The study identifies an implementation gap between halal awareness and operational practices, driven by limited managerial capacity and halal literacy. Furthermore, halal certification is often interpreted as symbolic compliance rather than a substantive supply chain management system. This study contributes to the HSCM literature by providing qualitative insights into MSME practices and by highlighting the interplay among values, perceptions, and managerial capability in shaping halal supply chain implementation.